Perayaan Tabuik dan Tabot: Jejak Ritual Keagamaan Islam SyiÃ¢â¬â¢ah di Pesisir Barat Sumatra - -, Asril (PANGGUNG, 2013)
ABSTRACTÃÂ This paper discusses the origin of Tabuik and Tabot ceremonies in Sumatera which possess influ- ence from religious ceremony of Syiah community in Persia (Iran). The aim of the research is to figure out the acculturation which has occurred between the Arabian (Middle East) and local cultures. The research uses analytic descriptive method through literature study. The result of the research shows that Tabuik and Tabot ceremonies are carried out as a ritual to commemorate the death of Husein in Syiah community which has become theological religious main ritual, and its spread to the west coast Sumatera (Pariaman and Bengkulu) has changed the theological value into cultural ritual, even in some cases it only becomes a cultural performance.ÃÂ Keywords: Tabuik and Tabot ceremony, religious ritualÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Tulisan ini membahas tentang asal-usul perayaan Tabuik dan Tabot di Sumatera yang mendapat pengaruh dari ritual keagamaan kaum SyiÃ¢â¬â¢ah di Persia (Iran). Tujuan penelitian ini untuk mengetahui sejauh mana akulturasi yang terjadi antara pengaruh budaya jazirah Arab (Timur Tengah) tersebut dengan budaya lokal. Penelitian ini menggunakan metode deskriptif analitis melalui studi kepustakaan. Hasil penelitian menunjukkan bahwa pera- yaan Tabuik dan Tabot dilaksanakan sebagai ritual mengenang kematian Husain di kalang- an penganut Islam SyiÃ¢â¬â¢ah yang menjadi ritual utama keagamaan yang bersifat teologis, dan penyebarannya ke pantai Barat Sumatra (Pariaman dan Bengkulu) mengalami ÃÂ perubahan nilai dari teologis menjadi bentuk ritual budaya, bahkan dalam beberapa kesempatan ha- nyaÃÂ  menjadi pertunjukan budaya saja.ÃÂ Kata kunci: upacara Tabuik danTabot, ritual keagamaan